Decentralisation, collaboration and diversity in social insurance benefit delivery in Thailand - Chaichakan, Chatthip (The University of Edinburgh, 2015)
This research provides a Thai case-study of social insurance benefit delivery (SIBD) and of the tension between the international norm of a standardized and centralised system and recent trends to diversified and locally responsive public service delivery. Thailand has been chosen as an example of decentralised and diversified SIBD since regional variation of its SIBD seemingly occurred after a more general decentralisation policy had been introduced in the country. Thus, this research examines the extent to which SIBD diversity exists in the way that decentralisation has been implemented in Thailand since the late 1990s. Built upon four theoretical perspectives (social insurance, collaborative public management, decentralisation, and inter-organisational relations) the conceptual framework uses three models of SIBD diversification (Weberian, customer-oriented, and strategic) to explain diversified patterns of SIBD in Thailand. The thesis is a multi-site case study research. Out of 76 Thai provinces, four provinces in the North were purposively selected to typify three socio-economic areas: commercial (Chiang Mai), industrial (Lamphun), and agricultural (Phrae, Nan). Employing qualitative methodology, a mixed method of data collection was undertaken with two major methods: interview with key actors (e.g. government officials, employers, employees) and documentary research (e.g. official reports, minutes of meetings, government plans and strategies). Further, in addition to analyzing content in texts (transcripts, documents), positional mappings and coding were carried out to illustrate the broad patterns of the phenomena studied. This research found that not only decentralisation but also inter-organisational collaboration has impacts on SIBD diversification. Political variables such as national and provincial elites were also investigated but they are evidently not predictors of the diversity. Indeed, decentralisation is a key factor of SIBD diversity which is evident in two of the provinces studied (Chiang Mai, Phrae). In Chiang Mai, being only slightly decentralised, SIBD rigidly follows national norms and routine patterns. In contrast, in Phrae, being highly decentralised, SIBD is highly diversified, especially because of an innovative SIBD project operating in the province. However, this research also finds that collaboration is a key factor of SIBD diversity in the other two provinces (Lamphun, Nan). In Nan, although similar to Chiang Mai with regard to low decentralisation, SIBD has become highly diversified as original and innovative SIBD projects in the province evidently involve several collaborative activities. In Lamphun, while being moderately decentralised, SIBD is just slightly diversified, in congruence with the low level of collaboration in the province. This research concludes that even in uniform systems SIBD can be very different reflecting the variable impact of local initiatives which are evidently results of decentralisation and/or collaboration.
Keywords: social insurance; social security; decentralisation; collaboration